The Relationship of Spirituality with Coping Mechanism in Patients with Type 2 Diabetes Mellitus in Sukabumi Regency, Indonesia - Rosliana Dewi; Ryan Taufik Hidayat; Ady Waluya; Johan Budhiana; Syiva Dwi Fatmala (STIKep PPNI Jawa Barat, 2023)
Aim: Apart from the obvious health consequences, diabetes mellitus leads in unfavorable psychological responses that can lead to emotional problems. Individual coping techniques for lowering stress and making treatment decisions in which spirituality plays a significant role. The study aimed was to determine the relationship between spirituality and the coping mechanisms of type 2 diabetes mellitus patients. Methods: This is correlational study with cross-sectional approach. Total sampling was used to collect data from 54 people diagnosed with type 2 diabetes. The spirituality instrument uses the Daily Spiritual Experience Scale (DSES) and the coping mechanism uses The Brief Cope. Statistical analysis using chi-square. Results: The results showed that most respondents had moderate spirituality (59,3%) and adaptive coping mechanisms (55.6%). The chi-square test results obtained a P-value of 0.008, so there is a relationship between spirituality and coping mechanisms in type 2 DM patients. Conclusion: The results showed that most of the respondents had moderate spirituality and adaptive coping mechanisms. Spirituality and adaptive coping skills are predicted to be enhanced by nurses, particularly in populations at risk for chronic disease.